1977
DOI: 10.1038/bjc.1977.32
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer: age at registration and age at death

Abstract: Summary.-Age-adjusted mortality from lung cancer rose rapidly in both males and females in Hong Kong from [1960][1961][1962][1963][1964][1965][1966][1967][1968][1969][1970][1971][1972]. The relative frequency of epidermoid carcinoma increased in male bronchial biopsies but not in lung biopsies, resections, or autopsies; there was a decline in small-cell anaplastic carcinoma. In both males and females the ratio of Kreyberg Group I (epidermoid and small-cell anaplastic) to Group II (adenocarcinoma and carcinoid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A recent early intervention study [21] (abdominal aortic aneurysm screening) reported improvements in survival; however (as previously observed by another author [22]), the results revealed no difference in age at death between invited and control groups. The other example exists in a prescreening population in cervical cancer [23]; the authors of this manuscript from 1977 observed that the average age of death was similar regardless of stage and age at diagnosis. The implications of our findings are that in a population of high socio‐economic deprivation, early intervention and aggressive attempts at curative surgery do not appear to be justified if the aim is improvement in overall life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent early intervention study [21] (abdominal aortic aneurysm screening) reported improvements in survival; however (as previously observed by another author [22]), the results revealed no difference in age at death between invited and control groups. The other example exists in a prescreening population in cervical cancer [23]; the authors of this manuscript from 1977 observed that the average age of death was similar regardless of stage and age at diagnosis. The implications of our findings are that in a population of high socio‐economic deprivation, early intervention and aggressive attempts at curative surgery do not appear to be justified if the aim is improvement in overall life expectancy.…”
Section: Discussionmentioning
confidence: 99%